THE INFLUENCE OF SOCIAL MEDIA MARKETING STRATEGY ON CONSUMER BUYING BEHAVIOR IN THE AIRLINE INDUSTRY IN KENYA (Cuea Journal of Business and Economics, 2025)
The airline industry in Kenya faced significant challenges in establishing competitive advantage within an increasingly digitalized market environment, with African airlines holding only 36.4% of intercontinental capacity compared to 63.6% by non-African carriers. Digital technologies had transformed consumer buying behavior, creating challenges for carriers lacking sophisticated digital marketing capabilities. The target population comprised approximately 33,425 daily airline passengers. The study used stratified random sampling to obtain a sample size of 384 participants. Data were collected using structured questionnaires and analysed using SPSS version 28.0, employing descriptive statistics, correlation analysis, simple regression, multiple regression, and moderated multiple regression analysis. The study achieved a response rate of 87.0% with 334 usable questionnaires. Simple regression analysis revealed that social media marketing strategy individually demonstrated the strongest explanatory power for consumer buying behavior variance, followed by search engine optimization strategy, content marketing strategy, and influencer marketing strategy. Multiple regression analysis showed that all digital marketing strategies had significant positive effects on consumer buying behavior, with social media marketing strategy showing the strongest effect, followed by search engine optimization strategy, content marketing strategy, and influencer marketing strategy. Digital literacy significantly moderated all relationships, meaningfully enhancing the model's explanatory power when interaction terms were included. All interaction effects were statistically significant across all digital marketing strategies. The study concluded that digital marketing strategies were effective predictors of consumer buying behavior in Kenya's airline industry, and digital literacy enhanced their effectiveness among more digitally proficient consumers. The study recommended that airline companies should develop integrated digital marketing strategies that prioritize social media engagement and search engine optimization while implementing tiered approaches that accommodate varying digital literacy levels among their target consumers.